2007
DOI: 10.1016/j.ijid.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infective endocarditis in Tunisia: a 10-year multicenter retrospective study

Abstract: Infective endocarditis is still frequently associated with rheumatic disease among young adults in Tunisia, with a high frequency of negative blood cultures and high in-hospital mortality, given that the population affected is relatively young.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
48
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 22 publications
12
48
3
1
Order By: Relevance
“…These two microorganisms have been reported as main etiological agents in 13-49% and 20-63% of the cases with native valve endocarditis, respectively (5,10,12). However, in our study cohort staphylococci and enterococci were the most frequently isolated causative agents in IE with the incidences of 29% and 11%, respectively.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…These two microorganisms have been reported as main etiological agents in 13-49% and 20-63% of the cases with native valve endocarditis, respectively (5,10,12). However, in our study cohort staphylococci and enterococci were the most frequently isolated causative agents in IE with the incidences of 29% and 11%, respectively.…”
Section: Discussioncontrasting
confidence: 48%
“…These changes are mainly being attributed to a number of factors including a marked reduction in the incidence of acute rheumatic disease and congenital heart disease, increase in cases of degenerative valvular disease, increasing patient longevity, increased use of invasive procedures and implanted medical devices (prosthetic valves, pacemaker, ICD and central vascular catheters etc.) (5,12). In a recent study conducted by Leblebicioğlu et al (14) from Turkey the mean age for IE was 45 years (112 adult patients), and in a study from Turkey by Çetinkaya et al (10) the patients were under the age of 40 years (228 patients).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although IE patients included in the present study manifested with a wide range of signs and symptoms, in consistent with the previous studies, [7,8,[11][12][13][14][15][16][17][18] the most common symptom was fever (86.7%), while the most common physical examination finding was murmur (88.1%). The patients who received the diagnosis of IE within the first 30 days following symptom onset accounted only for 53.8% of the study population.…”
Section: Discussionsupporting
confidence: 88%
“…[11,12] The mean age of patients at IE onset is as low as 32 years in countries such as Tunisia and India. [13,14] Studies performed in Turkey in different time points reported the mean age at disease onset varying between 45 and 47 years. [15][16][17] Furthermore, IE develops more frequently in men; however, the reason underlying higher proportion of men is poorly understood, and the Guidelines on the prevention, diagnosis, and treatment of IE published by the European Society of Cardiology estimates a maleto-female ratio of 2:1.…”
Section: Discussionmentioning
confidence: 99%